2017
DOI: 10.1038/s41598-017-01600-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced NF-κB nuclear translocation is primarily dependent on MyD88, but TNFα expression requires TRIF and MyD88

Abstract: TLR4 signalling through the MyD88 and TRIF-dependent pathways initiates translocation of the transcription factor NF-κB into the nucleus. In cell population studies using mathematical modeling and functional analyses, Cheng et al. suggested that LPS-driven activation of MyD88, in the absence of TRIF, impairs NF-κB translocation. We tested the model proposed by Cheng et al. using real-time single cell analysis in macrophages expressing EGFP-tagged p65 and a TNFα promoter-driven mCherry. Following LPS stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 52 publications
3
92
1
Order By: Relevance
“…Profiles of de novo synthesized intracellular TNFα under the stimulation of LPS in the presence of Golgiplug ™ demonstrated that the TNFα production increased around one hour after the stimulation (Figure 2). At around the same time, the IκBα concentration reached its minimum, which is consistent with experimental observations in the literature [46][47][48]. Subsequently, the IκBα concentration increased due to the induction of IκB transcript (IκB t ) by nuclear translation of NFκB, while the TNFα production rate slowed down beyond 4 h of LPS stimulation (Figure 2).…”
Section: Resultssupporting
confidence: 90%
“…Profiles of de novo synthesized intracellular TNFα under the stimulation of LPS in the presence of Golgiplug ™ demonstrated that the TNFα production increased around one hour after the stimulation (Figure 2). At around the same time, the IκBα concentration reached its minimum, which is consistent with experimental observations in the literature [46][47][48]. Subsequently, the IκBα concentration increased due to the induction of IκB transcript (IκB t ) by nuclear translation of NFκB, while the TNFα production rate slowed down beyond 4 h of LPS stimulation (Figure 2).…”
Section: Resultssupporting
confidence: 90%
“…Activated NF-κB translocates to the nucleus, thus we examined the effect of C-miR146a on the localization of NF-κB in LPS-treated RAW264.7 cells expressing NF-κB/p65-eGFP fusion protein. 27 Confocal microscopy confirmed that C-miR146a, but not C-scrRNA, efficiently blocked the nuclear translocation of NF-κB ( Figure 2C). Correspondingly, the C-miR146a reduced the NF-κB DNA-binding activity in nuclear extracts from RAW264.7 and MDSL cells as measured using gelshift assays ( Figure 2D).…”
Section: C-mir146a Mimic Targets Upstream Regulators Of Nf-κb Signalingmentioning
confidence: 75%
“…2C, D). NF-kB proteins are well-known to be key TFs involved in control of the immune response, for instance by inducing TNF-a expression in primary human macrophages in response to TLR agonists (34,35,53). The finding that IS-induced phosphorylation of NF-kB p65 on Ser536 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Although multiple TFs are involved in inflammatory and immune responses, the NF-kB family plays a central role in inflammation, including in the induction of TNF-a gene transcription, especially in monocytes and macrophages (33)(34)(35). Therefore, to access whether IS activates Figure 1.…”
Section: Is-induced Tnf-a Expression Is Regulated By Ahr-mediated Resmentioning
confidence: 99%